Separation axioms in intuitionistic fuzzy topological spaces - Singh, A.K.; Srivastava, R. (My University, 2012)
In this paper we have studied separation axioms T i, i = 0, 1, 2 in an intuitionistic fuzzy topological space introduced by Coker. We also show the existence of functors B: IF - Top → BF - Top and D: BF - Top → IF - Top and observe that D is left adjoint to B.
Keywords: intuitionistic; topological space; fuzzy